Aplicação de programa computacional no dimensionamento de volume de reservatório para sistema de aproveitamento de água pluvial da cidade de Ponta Grossa, PR - Moruzzi, Rodrigo Braga [UNESP]; Oliveira, Samuel Conceição de [UNESP] (My University, 2010)
The main aim of this paper was to use the REZZ software to calculate the tank volume rainwater harvesting system. For this purpose, rain data of Ponta Grossa-PR-Brazil were used considering different statistical treatment (average, 75%, 85%, 95% and 99% of confidence) and different roof areas (50, 80, 120 and 200 m2). The harvesting system was considered only for toilet flush in households with 3, 4 and 5 inhabitants. There were applied the following methods/concepts: Flow equalization (Rippl); Brazilian method as well the English and German practical methods. Further, the mass-balance was simulated for some conditions. All considered methods are described in NBR15527/07, the Brazilian standard for rainwater harvesting. As expected, the results pointed out for huge differences depending on the choice method and the statistical treatment of the rain data. The REZZ appliance showed to be useful thus permitting to set different conditions and to obtain rapid results in order to assist designers to adopt the best cistern volume for each particular case.

O objetivo do artigo foi aplicar o programa computacional REZZ para dimensionamento de reservatório de sistema de aproveitamento de água pluvial. Para tal, foram utilizados os dados pluviométricos da cidade de Ponta Grossa-PR para valores médios de precipitação e aqueles referentes aos percentis de 75, 85, 95 e 99% em residências com 50, 80, 120 e 200 m2 de área de cobertura para consumo em vasos sanitários considerando 3, 4 e 5 habitantes por domicílio. Foram empregados os seguintes métodos: Equalização de Vazão (RIPPL), Método Brasileiro (Azevedo Netto) e os Métodos Práticos Alemão e Inglês. Adicionalmente, o volume de água disponível no reservatório foi verificado por meio de balanço hídrico utilizando o Método da Simulação. Todos os métodos utilizados constam na NBR15527/07. Os resultados apontaram para grandes variações de volume de acordo com o método e o tratamento estatístico empregados. O uso do REZZ propiciou agilidade na obtenção dos volumes dos reservatórios nos diferentes métodos.
Application of software for cistern volume calculation in rainwater harvesting system in Ponta-Grossa-PR, Brazil
Keywords: Rainwater harvesting; Cistern; Software; Aproveitamento de água pluvial; Reservatório|Programa computacional